AGILE HR PRACTICES AND THEIR IMPACT ON ORGANIZATIONAL ADAPTABILITY AND INNOVATION - Linna Dhah Liawati; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates how Agile HR practices enhance organizational adaptability and innovation in volatile business environments. Through qualitative analysis of interviews and organizational documents, we identified four core components of Agile HR: Continuous Performance Fluidity, Iterative Talent Mobilization, Just-in-Time Learning Ecosystems, and HR as an Enabling Scaffold. Our findings demonstrate that these practices collectively create a synergistic system that drives organizational adaptability through two primary mechanisms - increased strategic responsiveness and enhanced operational resilience. The research reveals significant improvements in key adaptation metrics, including 85% faster strategic realignment and 78% more efficient talent deployment. Furthermore, the study establishes that Agile HR fosters innovation by cultivating psychological safety and empowerment through continuous feedback and autonomous work structures. This research provides organizations with empirical evidence and a practical framework for transforming HR from an administrative function into a strategic driver of agility and competitive advantage in the digital economy.